2004
DOI: 10.1063/1.1821497
|View full text |Cite
|
Sign up to set email alerts
|

Vibronic spectroscopy of unsaturated transition metal complexes: CrC2H, CrCH3, and NiCH3

Abstract: Vibronically resolved resonant two-photon ionization and dispersed fluorescence spectra of the organometallic radicals CrC(2)H, CrCH(3), and NiCH(3) are reported in the visible and near-infrared wavelength regions. For CrC(2)H, a complicated vibronic spectrum is found in the 11 100-13 300 cm(-1) region, with a prominent vibrational progression having omega(e) (')=426.52+/-0.84 cm(-1), omega(e) (')x(e) (')=0.74+/-0.13 cm(-1). Dispersed fluorescence reveals a v(")=1 level of the ground state with DeltaG(1/2) (")… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 61 publications
2
27
0
Order By: Relevance
“…24,26 The ground state of CrCCH is 6 Σ + . As illustrated in Figure 4, each rotational level for this term, indicated by N, is split into six fine structure components, labeled by J.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…24,26 The ground state of CrCCH is 6 Σ + . As illustrated in Figure 4, each rotational level for this term, indicated by N, is split into six fine structure components, labeled by J.…”
Section: Resultsmentioning
confidence: 99%
“…23 Vibrationally resolved spectra of NiCH 3 has also been recorded. 24 Spectroscopic studies of chromium-bearing molecules have been almost exclusively the work of Morse and collaborators. These authors have recorded vibrationally resolved spectra of the 6Ẽ -X 6 A 1 transition of CrCH 3 and thẽ A 6 Σ + -X 6 Σ + system of CrCCH 24 using resonant two-photon ionization (R2PI) methods; they also measured the 3 Σ − -X 3 Σ − system of CrC with rotational resolution.…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneously, C2H radical prefer to maintain its integrity when C 2 H radical interacts with Fe, Cr, Yb, Co and Au [25,26,[27][28][29].…”
Section: Isomers C-h Rocking Vibration C-c Stretching Vibration C-h Smentioning
confidence: 99%
“…High-level ab initio calculations, using the CPd-G2 thaw and CP-G2 composite computational procedures (combined with spin projection techniques when appropriate), are used to explore the bonding between the metal mono cations Na . Brugh [26] found that both the ground and the excited state of CrC 2 H had liner structure and their vibronic spectrum were complicated in the 11100-13300 cm −1 region. The first spectroscopic identification and characterization of YbC 2 H has been reported by combining resonance-enhanced two photon ionization, laser-induced fluorescence and photoionization efficiency spectroscopy with density functional calculations [27].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, 53 lines of the 0-0 band of the A-X system of the minor isotopomer 50 CrH (natural abundance 4.3%) were recorded during an investigation of the related CrC 2 H molecule, and these are reported here as well. The study of CrC 2 H has been published elsewhere ( Brugh et al 2004). …”
Section: Introductionmentioning
confidence: 99%